Armenian Genocide Survivors: The Strunga Orphanage in Romania - Lidia Prisac (ՀՀ ԳԱԱ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
This article examines the history of the 200 children rescued from massacres that took place during the Armenian Genocide, who found shelter in Greater Romania (1918-1940), in the Strunga orphanage, which was open for three years, from 1923 to 1926. The Strunga orphanage history approach reflects the dimensions of humanitarian assistance in the Kingdom of Romania on the issue of Armenian refugees, particularly on the fate of children after the genocide. The reconstruction of this orphanage history is based on historical sources, such the Album of Orphans (1923), archive documents and articles from the contemporary press published by the Armenian minority in interwar Romania. In general, the humanitarian dimensions of Armenian community support in Romania offered the orphans the possibility of rehabilitation after the genocide and adaptation to the new social environment that Romania represented.
Keywords: Armenian genocide; Political science; Sociology; Literature; Law